Law and urban growth : civil litigation in the Boston trial courts, 1880-1900 - Silverman, Robert A., 1947- (Princeton legacy library, 1981)
This in-depth study of civil trial courts in any American city during the nineteenth century. Examining cases brought before the Boston civil courts between 1880 and 1900, Robert Silverman shows how the business of these tribunals mirrors social and economic changes within the urban community and how these changes made the 1890s a turning point in the function of law. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.